2012
DOI: 10.1111/j.1365-2125.2011.04125.x
|View full text |Cite
|
Sign up to set email alerts
|

Model‐based design of rituximab dosage optimization in follicular non‐Hodgkin's lymphoma

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The concentration-effect relationship of rituximab in follicular lymphoma (FL) was previously described using pharmacokinetic-pharmacodynamic (PK-PD) modelling.• The influence of genetic polymorphism of FCGR3A on rituximab efficacy in FL patients was included in this PK-PD model.• Previous studies suggest that increasing the dose of rituximab and/or the number of infusions may lead to a better clinical response in FL. WHAT THIS STUDY ADDS• The previously validated PK-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…7,13,35 Higher frequency of 375 mg/m 2 rituximab infusions did not result in better outcomes in all patients as compared with the classical regimen. 4,36 The SEXIE-R-CHOP-14 study demonstrated that an increased rituximab dose of 500 mg/m 2 in elderly male patients resulted in improved outcome.…”
Section: Discussionmentioning
confidence: 80%
“…7,13,35 Higher frequency of 375 mg/m 2 rituximab infusions did not result in better outcomes in all patients as compared with the classical regimen. 4,36 The SEXIE-R-CHOP-14 study demonstrated that an increased rituximab dose of 500 mg/m 2 in elderly male patients resulted in improved outcome.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, the fact that NK cells from F/F donors require higher concentrations of RTX for ADCC in vitro compared with V/V carriers 87 suggests that increasing RTX doses in vivo may overcome the effect of FcγRIIIA polymorphisms. 94 An effect of FcγRIIIA polymorphism has, however, not been observed in CLL 95 or in FL patients treated with RTX and chemotherapy, probably due to dilution of the effect by standard drugs. 96 In large studies of DLBCL treated with R-CHOP, there are reports of a trend for better response of V/V and V/F patients compared with F/F.…”
Section: The Interaction Between Rtx Pd and Pkmentioning
confidence: 99%
“…Few studies have investigated the pharmacokinetics of rituximab when administered with other drugs or at different intervals. 42,43 The PK profile of rituximab when administered as part of an R-CHOP chemotherapy was recently reported by Blasco et al 44 They found that PK parameters were similar to those described for studies in the absence of chemotherapy. In addition, the authors did not observe any intra-subject variation in pharmacokinetic parameters over the treatment period.…”
Section: Pharmacokinetics Of Rituximabmentioning
confidence: 63%